Comparison between A-mode and B-mode ultrasound in local hyperthermia monitoring - Maizatul Nadwa Che Aziz, 1990-, author 620288; Maheza Irna Mohamad Salim, 1983-, supervisor 516061; Fakulti Biosains dan Kejuruteraan Perubatan (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Kejuruteraan (Bioperubatan))